Living in uncertainty after a pituitary macroadenoma: a case study - Redondo-Sáenz, Diego (Universidad de Sonora, 2019)
Introduction: The Theory of Uncertainty in Illness is a middle-range nursing theory that explains the processes faced by people with chronic illnesses, in order to achieve adaptation. This theory describes antecedents of uncertainty, appraisal mechanisms, and coping strategies to adapt to new conditions. Objective: Demonstrate the integration of the nursing process, standardized language, and the Theory of Uncertainty in Illness involved in the care of a person with physical and psychosocial complications after a pituitary macroadenoma. Methodology: Data was collected through interviews with the patient, physical examination, and medical record. Mishel’s Theory of Uncertainty in Illness, standardized languages to describe diagnosis, interventions, results and scientific evidence were used to develop the care plan. Presentation of the case: The Theory of Uncertainty allowed selecting the main diagnosis, that is, ineffective coping related to uncertainty, which was addressed with the following NICs, improve coping and learning, illness process; the results measured were NOC, stress level and knowledge, chronic illness management. The effectiveness of this approach was reflected in the improvement of the indicators. Conclusions: The identification of a theory that can explain findings and guide the interventions enhances the quality of the nursing care. This integration facilitates a personalized and evidence-based nursing care.